From integration to integrity administrative ethics and reform in the European Commission - Cini, Michelle 1963- (Manchester Univ. Press, 2007)
This book examines how the European Commission has addressed concerns about its ethical standards since 1999.
Keywords: European Commission -- Ethics; European Commission -- Officials and employees; Europäische Kommission; Labor discipline -- Europe; Politische Ethik; Verhaltenskodex; Europa